2022
DOI: 10.1371/journal.pone.0262919
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of social media communities for caregiver information support in stroke recovery: An analysis of content and interactions

Abstract: Background Caregivers often use the internet to access information related to stroke care to improve preparedness, thereby reducing uncertainty and enhancing the quality of care. Method Social media communities used by caregivers of people affected by stroke were identified using popular keywords searched for using Google. Communities were filtered based on their ability to provide support to caregivers. Data from the included communities were extracted and analysed to determine the content and level of inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(40 citation statements)
references
References 35 publications
0
39
0
1
Order By: Relevance
“…While there is an increased interest in researching health related quality of life in MG patients [25], the impact of peer-to-peer support has, to date, been largely unaddressed within the scienti c literature on the subject. In focusing on such, this study contributes to a growing body of literature investigating online health communities targeted at patient populations with speci c conditions including breast cancer [26], diabetes [27], stroke [28,29] and numerous rare diseases [1,3,18,30,31]: the results of which have shown that social media is an important information resource for many in the affected populations MG is no different in this regard. The high need for information amongst those affected by MG was recently demonstrated in a study analysing emails written to a specialised treatment centre and patient organisation body [32] and it appears that this need is not restricted to these channels.…”
Section: Discussionmentioning
confidence: 99%
“…While there is an increased interest in researching health related quality of life in MG patients [25], the impact of peer-to-peer support has, to date, been largely unaddressed within the scienti c literature on the subject. In focusing on such, this study contributes to a growing body of literature investigating online health communities targeted at patient populations with speci c conditions including breast cancer [26], diabetes [27], stroke [28,29] and numerous rare diseases [1,3,18,30,31]: the results of which have shown that social media is an important information resource for many in the affected populations MG is no different in this regard. The high need for information amongst those affected by MG was recently demonstrated in a study analysing emails written to a specialised treatment centre and patient organisation body [32] and it appears that this need is not restricted to these channels.…”
Section: Discussionmentioning
confidence: 99%
“…The information preferred by the caregiver is expected to be personalized to individual situations and health literacy; with a majority of caregivers preferring visual demonstrations. The importance of visual demonstrations for the delivery of stroke information is not new, and has been discussed previously in a study by Lobo et al [ 19 ] as a preferred method to ensure maximum interaction. However, our findings show that the information provided is in the form of generic pamphlets and brochures with limited explanation from the healthcare professional that led to confusion.…”
Section: Discussionmentioning
confidence: 99%
“…These social media platforms were selected as it has in the past been used by organizations and individuals to actively engage and participate in healthcare. Moreover, it can promote better health management and decision-making processes [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…The companions of patients who have suffered stroke need subsidies to increase their interaction with survivors and play their role as companions and thus assist patients to perform self-care supported (18) . Interventions that contribute to the supported selfmanagement of care demonstrate positive results for both companions and patients (19) .…”
Section: Discussionmentioning
confidence: 99%